Pewarisan Karakter Kualitatif Cabai Hias Hasil Persilangan Cabai Besar dan Cabai Rawit - Hapshoh, Siti; Syukur, Muhamad; Wahyu, Yudiwanti; Widodo, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTThe fruit of ornamental chili functioned as ornamental as well as for consumption, and therefore it requires diversity of traits for selection process. Information on inheritance pattern of the traits are needed for effective selection. The ideotype of ornamental chili are shortened internode that form a bouquet of flowers, erect fruit orientation and contain anthocyanins for attractive appearance. The research was aimed to study qualitative characters inheritance associated with shortened internode, fruit orientation and anthocyanins content. This study used 6 population including female parent (P1) which has anthocyanin in flower parts, the male parent (P2) bird pepper which has the character of a shortened internode, F1, F1R, BCP1, BCP2, and F2. Data were analyzed with Chi-square test to determine the Mendelian ratio in the F2 population. The results showed that there were characters that was controlled by one gene or two genes. Shortened internode and erect fruit orientation were controlled by a single recessive gene with a ratio of 1:3. On the other hand the color of anthocyanin in the anther stem was controlled by one dominant gene with a ratio of 3:1. The characters controlled by two genes that were dominant and recessive epistasis was the color of anthocyanins in the anther with the ratio 13:3.Keywords: Mendelian ratio, antosianin, shortened internode